Considerations on the management and prevention of virus and virus-like diseases of stone fruits in Uruguay - Maeso, Diego (Agrociencia Uruguay, 2021)
The following agents were reported in Uruguay in stone fruit trees: PNRSV (Prunus necrotic ringspot virus), PDV (Prune dwarf virus), ACLSV (Apple chlorotic leafspot virus), ApMV (Apple mosaic virus) and PLMVd (Peach latent mosaic viroid). PNRSV and PDV are widespread, their plant to plant transmission in the orchard and by seed was confirmed and causes important losses in nurseries and commercial plantations. ACLSV, ApMV y PLMVd are not widely disseminated, and PPV (causal agent of sharka, Plum pox virus) was not found. Certification of fruit tree plants supervised by the INASE is mandatory. Healthy propagative materials of cultivars and rootstocks are available, but growers prefer the cheapest plants with less coverage of certification. A limited, uneven, and decreasing demand for healthy plants threatens the sustainability of the system. Phytosanitary requirements to prevent the entry of new pests (quarantine) are established by Ministry of Livestock, Agriculture and Fisheries. Official phytosanitary documents required are often difficult to obtain by the suppliers of new cultivars or rootstocks and the risk of pest introduction is high. For this reason, many countries have post entry quarantine stations where introduced plant materials are kept under surveillance until release to the industry. Some fruit producing regions that have important diseases perform plant eradication programs, control of vectors and replacement with certified plants; but, according to the current sanitary status of stone fruit trees in Uruguay, that would not be necessary yet. Conversely, it would be advisable to: 1) prevent the arrival of new pests, considering to set post quarantine plant stations, 2) keep an active surveillance to early detect sanitary problems, 3) encourage sanitary quality on certified plants and 4) develop new orchards using virus-free certified plants.